Does globalGAP certification promote agrifood exports? - Dela-Dem Doe Fiankor; Insa Flachsbarth; Amjad Masood; Bernhard Brümmer (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
With increasing global agrifood trade, private food standards and certifications have proliferated. Yet, their trade effects remain ambiguous. We provide further empirical evidence by assessing the effect of GlobalGAP certification on agrifood exports to high-value markets in EU and OECD countries. Empirically, we estimate a structural gravity model - that accounts for zero trade and endogeneity of certification - using a novel dataset of certified producers and land area cultivated to apples, bananas, and grapes from 2010 to 2015. While our results generally confirm the trade-enhancing effect of GlobalGAP certification for both developed and developing countries, we show that the effects vary across products.
Keywords: F14; Q17; Q18; 330; agricultural trade; GlobalGAP; private food standards; gravity model